Selexipag-based triple combination therapy improves prognosis in Chinese pulmonary arterial hypertension patients - Cui, Xiaopei; Lu, Weida; Zhang, Deyuan; Qie, Liangyi; Li, Haijun; Li, Xiao; Liu, Hui; Ji, Qiushang (Frontiers in Cardiovascular Medicine, 2022)
Selexipag is an oral selective prostacyclin receptor agonist approved for treatment of patients with pulmonary arterial hypertension (PAH). In the present study, we aim to assess the safety and efficacy of selexipag in triple combination therapy with ERAs and PDE5is for Chinese PAH patients. A single center retrospective study was performed on group 1 PAH patients (n = 68) initiating triple combination therapy with selexipag from February 1, 2020 to August 31, 2021 in Qilu Hospital of Shandong University (Shangdong, China). Aldolescents, children and PAH patients with unrepaired congenital heart disease were excluded. The French pulmonary hypertension network (FPHN) non-invasive risk assessment, echocardiogram parameters, and clinical data, including tolerability, safety, and death/hospitalization events associated with PAH, were collected. Of the 68 patients, 31 (45.6%) patients had tolerable side effects while only a single patient discontinued selexipag due to severe diarrhea. In the analysis of the efficacy set of 62 patients, the median selexipag treatment time from selexipag initiation to last risk assessment was 27 (21, 33) weeks. Compared to baseline parameters, the percentage of WHO FC III/IV decreased from 77.4 % (48) to 24.2 % (15) (p = 0.000), median 6MWD increased 82 m (from 398 (318, 450) to 480 (420, 506) m; p = 0.000), and NT-proBNP levels decreased from 1216 (329, 2159) pg/mL to 455 (134, 1678) pg/mL (p = 0.007). Patients who improved to 3 low-risk criteria increased from 9.7% to 38.7%. RV diameter also decreased and was accompanied by an improved TAPSE. Patients transitioning from subcutaneous treprostinil to selexipag continued to show improvements in WHO FC, 6MWD (404 ± 94 m vs 383 ± 127 m) and NT-proBNP levels (2319 ± 2448 vs 2987 ± 3770 pg/mL). Finally, the one-year event free survival rate was 96.7% for patients initiating the triple combination therapy within 3 years of PAH diagnosis. In conclusion, Triple combination therapy with selexipag was safe and effective in Chinese PAH patients, which was confirmed by acceptable tolerability, and improved exercise capacity, right heart function, risk assessment and prognosis.